2009
DOI: 10.1007/s10750-009-9915-5
|View full text |Cite
|
Sign up to set email alerts
|

Relating macroinvertebrate community structure to environmental characteristics and sediment contamination at the scale of the St. Lawrence River

Abstract: There is still no assessment of the impact of sediment chemicals and environmental conditions on macroinvertebrates at the scale of the St. Lawrence River. In order to assess these impacts in the fluvial section of the St. Lawrence River including the Montreal harbour, the community structure of macroinvertebrates using different taxonomic aggregations (genus and family) and taxa attributes (abundance, presence-absence, indicator taxa) was assessed. The goal of the study was to determine the indicator taxa of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 41 publications
(52 reference statements)
0
26
0
Order By: Relevance
“…Even if data were available about the response of single taxa to heavy metal concentration in lakes (Rizzo et al 2011) , their influence on community composition is very poorly known; often the information is based on studies with larger taxonomic resolution carried out in rivers (Masson et al 2010), little information is available about species response in lakes.…”
Section: Discussionmentioning
confidence: 99%
“…Even if data were available about the response of single taxa to heavy metal concentration in lakes (Rizzo et al 2011) , their influence on community composition is very poorly known; often the information is based on studies with larger taxonomic resolution carried out in rivers (Masson et al 2010), little information is available about species response in lakes.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have reported that habitat conditions can have a stronger influence on macroinvertebrate communities than sediment contamination [6,[54][55][56]. For example, in a comprehensive study of the factors that structure benthic invertebrate assemblages in the St. Lawrence River, Masson et al [6] found that sediment contamination alone explained a very low percentage of the total variance of taxa (< 2%). However, environmental characteristics, such as sediment organic content and percent sand, explained between 13 and 15% of macroinvertebrate community structure.…”
Section: Spatial Distribution Of Macroinvertebrates In Relation To Crlmentioning
confidence: 99%
“…This paper focuses on the potential impacts of radiological contamination in sediment on benthic macroinvertebrate communities in the Ottawa River in a localized area referred to as the 'footprint' compared to upstream and downstream conditions. Macroinvertebrate communities have been extensively used for biomonitoring of freshwater systems [3][4][5][6]. Benthic invertebrates in direct contact with and consuming contaminated sediments are often the biota highly exposed to sediment-associated contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Macroinvertebrate communities within the wastewater plume are characterized by the variations in the presence of certain nematodes, flatworms, poriferans, dipterans (Chironomus, Dicrotendipes, Tribelos), gastropods (Bithynia), isopods (Caecidatea, Lirceus), and tubificid oligochaetes (Hyodrilus, Quistadrilus and Limnodrilus) (Masson et al 2010). The oligochaetes, in particular, are tolerant of organic pollution (Aston 1973).…”
Section: Macroinvertebratesmentioning
confidence: 99%
“…Myxozoans typically have complex life cycles that include both oligochaetes and fish. Oligochaete density increases at sites exposed to municipal effluents downstream of Montreal compared to those upstream (Marcogliese et al 2009;Masson et al 2010). Thus, myxozoans are good indicators of organic pollution and eutrophication.…”
Section: Fish Parasitesmentioning
confidence: 99%